Mentorship among healthcare researchers: a social network analysis - Bo Kim; Bo Kim; Erin A. Pleasants; Jennifer L. Sullivan; Jennifer L. Sullivan; Amy M. Linsky; Amy M. Linsky; Amy M. Linsky (Frontiers in Health Services, 2025)
IntroductionMentorship is an active workplace relationship between a mentor and a mentee, aimed at mutual career advancement, which is vital for both employee growth and organizational success. To improve their mentorship structures and processes, organizations must first assess their current practices. Thus, we developed and conducted a cross-sectional survey to evaluate mentorship among employees at a two-site federally funded health services research center.MethodsWe surveyed Center investigators and other employees (henceforth “staff”), gathering data on mentors, mentees, mentoring relationships, and satisfaction with the Center's mentoring infrastructure. We used social network analysis to examine both formal and informal mentoring relationships and assessed the association of employee connectedness in these networks with reported satisfaction.ResultsThere were 120 respondents (62.2% response rate). A greater percentage of investigators, compared to staff, had at least one formal mentor (55.8% vs. 25.0%) and one formal mentee (57.7% vs. 10.3%), and investigators had more informal mentors within the Center than staff (4.94 vs. 3.59, p = 0.0485). Investigators reported higher satisfaction with mentorship compared to staff (6.63 vs. 5.25, p = 0.002) and had more formal mentoring relationships with other investigators than staff had with other staff (0.06 vs. 0.01 degree centrality, p < 0.0001). Combining formal and informal mentorship across both investigators and staff, compared to formal mentorship alone, showed fewer degrees of separation (1.32 vs. 3.41 mean distance, p < 0.0001). For the combined formal and informal mentorship network across both investigators and staff, satisfaction with mentoring was associated with having more connections with network members who were connected with each other (r = 0.998, p < 0.0001).DiscussionTo foster connections among employees, research organizations may create opportunities for open communication and collaborative problem-solving. Our survey and findings are timely given the growing emphasis on mentorship's importance for successful careers, motivated employees, and workplace productivity.